Effects of synthetic hormone substitutes and genotypes on rooting and mini tuber production of vines cuttings obtained from white yam (Dioscorea rotundata, Poir) - Agele, S.O.; Ayankanmi, T.G.; Kikuno, H. (2010)
This study was designed to evaluate the effects of some root - promoting substances on rooting andmini tuber formation using vine cuttings obtained from two genotypes (TDr 335 and TDr 93 - 49) of whiteyam (D. rotundata). The ashes were obtained from rice straw, bamboo, Gliricidia sepium, dry leaves ofAzardiracta indica (neem), and 1% indolebutyric acid (IBA). These were powdered on the nodal woundsof vine cuttings before they were planted in planting media (carbonized rice husk). The plant asheswere mixed at 1, 3 and 5 g each in 100 ml of water. Coconut water was also diluted at 1, 5 and 10 ml in100 ml of water while pyroligneous acid (PA) was diluted (1 ml each in 500, 1000, 2000 and 3000 ml in5000 ml of water). Both dilutions were used to treat vine cuttings before planting in cups filled withcarbonized rice husk. The vine cuttings were sampled for rooting percentage, number of roots, rootlength and mini tuber initiation 21 days after treatment (DAT). The number and weight of tubersobtained from IBA and wood ash treated vines were not significantly different. The rice straw ash, IBAand neem leaves powder treated vines produced greater rooting percentage (above 70%) than percentrooting obtained from vines treated with other plant ashes. Rice straw ash (5% concentration) had thehighest rooting percentage (80%) relative to other plants ash concentrations. Higher rooting percentagewas obtained in coconut water diluted at 1 and 5% than 10 and 100% dilutions. Rooting percentagesfrom vine cuttings treated with pyroligneous acid (PA) dilutions were not better than control(unteeated). The rooting percentages obtained from vines treated with different concentrations of plantsashes, root - promoting substances and control in this study were not significantly different (P = 0.05),except in vine cuttings treated with 5 g rice straw ash in 100 ml of water. Higher values of rootingpercentage, number of roots, root length and mini tubers were obtained from genotype TDr 93 - 49compared with values recorded from vine cuttings obtained from the genotype TDr 335.